TRADE CREATION DAN TRADE DIVERSION ANTARA INDONESIA DAN NEGARA-NEGARA ASEAN-KOREA - Tresna Ritaningsih; Dedi Budiman Hakim; Sahara Sahara (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2014)
Indonesia has several free trade agreements with trading partners that aimed to eliminate tariff and non tariff trade barriers. One of the free trade agreements is ASEAN-Korea FTA. Trade agreement in goods in ASEAN-Korea FTA was agreed since 2007 and now it is entering the implementation phase. The objective of this research is to determine whether the ASEAN-Korea FTA would increase the trade flows between Indonesia and ASEAN-Korea’ countries by analyzing the impact of regional integration on trade creation and trade diversion. This research is utilized balance panel data including 13 countries from 1998-2012. The empirical result shows that all Indonesia's trading sectors experienced decline because of trade diversion and trade creation does not occur. Indonesia's import trading with the non-member countries of ASEAN-Korea is 68% lower than the existing trading. Key word: trade creation, trade diversion, free trade agreement, trade in goods